2017
DOI: 10.1111/cei.12941
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of the SERPING1 gene in Swiss patients with hereditary angioedema

Abstract: Hereditary angioedema with C1 inhibitor deficiency (C1-INH-HAE) is a rare autosomal dominant disease caused by mutations in the C1 inhibitor gene SERPING1. Phenotype and clinical features of the disease are extremely heterogeneous, varying even within the same family. Compared to HAE cohorts in other countries, the genetic background of the Swiss HAE patients has not yet been elucidated. In the present study we investigated the mutational spectrum of the SERPING1 gene in 19 patients of nine unrelated Swiss fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…Missense mutations in exon 7 and 8 were the most common mutations in our cohort. Mutation spectrum in SERPING1 gene is quite heterogeneous and more than 450 mutations spread over the entire gene have been reported so far 33,58–61 . Missense mutations have been reported to be the most common mutations in SERPING1 gene 8,62–64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Missense mutations in exon 7 and 8 were the most common mutations in our cohort. Mutation spectrum in SERPING1 gene is quite heterogeneous and more than 450 mutations spread over the entire gene have been reported so far 33,58–61 . Missense mutations have been reported to be the most common mutations in SERPING1 gene 8,62–64 .…”
Section: Discussionmentioning
confidence: 99%
“…Mutation spectrum in SERPING1 gene is quite heterogeneous and more than 450 mutations spread over the entire gene have been reported so far. 33,[58][59][60][61] Missense mutations have been reported to be the most common mutations in SERPING1 gene. 8,[62][63][64] while some populations have reported that nonsense or frameshift mutations are most common.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation spectrum in SERPING1 gene is quite heterogeneous and more than 450 mutations spread over the entire gene have been reported so far. 33,[56][57][58][59] Missense mutations have been reported to be the most common mutations in SERPING1 gene. 8,[60][61][62] while some populations have reported that nonsense or frameshift mutations are most common.…”
Section: Discussionmentioning
confidence: 99%
“…Switzerland, a neighboring country, has nearly the same number of inhabitants as Austria and similar numbers of C1‐INH‐HAE patients; an investigation yielded 111 affected patients, who are believed to constitute 70 % of all HAE patients in Switzerland . A handful of national studies have been performed on the prevalence of HAE.…”
Section: Discussionmentioning
confidence: 99%